Advanced age is associated with increased adverse outcomes in patients undergoing middle cerebral artery stenting - Wang, Gong; Liu, Juan; He, Shengrong; Zhang, Xi; Yang, Libai; Gao, Fei; Guo, Yu; Xu, Rui (Frontiers in Neurology, 2023)
Purpose: This study tried to evaluate whether advanced age has an increased incidence of major complications in patients undergoing MCA stenting. Methods: A total of 348 patients who underwent MCA stenting were reviewed from a prospectively maintained database. Ninety-day ischemic stroke, intracerebral hemorrhage, and death outcomes were compared among the young (≤ 40 years old), middle (41 to 60 years old) and old (≥ 61 years old) groups. Univariate analysis and multivariable logistic regression analysis were used to investigate different variables associated with 90-day major adverse events. Kaplan-Meier analysis was performed to determine long-term outcomes during follow-up. Results: The incidence of 90-day ischemic stroke was 9.26% in the old group, 2.86% in the middle group, and 0% in the young group (P = 0.024). The incidence of all 90-day major adverse events was 3.33% in patients ≤ 40 years old, 19.90% in patients 41 to 60 years old, and 24.07% in patients ≥ 61 years old, with statistical significance (P = 0.04). Advanced age was associated with increased 90-day ischemic stroke (OR = 1.074, 95% CI: 1.019-1.132, P = 0.007; adjusted OR: 1.071, 95% CI: 1.008-1.138, P = 0.026) and 90-day death (OR = 1.072, 95% CI: 1.012-1.135, P = 0.018; adjusted OR: 1.095, 95% CI: 1.015-1.182, P = 0.018). Meanwhile, advanced age was also associated with decreased long-term survival and ischemic stroke-free survival during follow-up. Conclusion: Our data indicated that MCA stenting in elderly patients is associated with a high risk of adverse events and should be cautiously considered.